EVALUATION OF THE HYPOGLYCAEMIC POTENTIAL OF KIGELIA AFRICANA FRUIT POWDER BEING SOLD IN MALAWIAN RETAIL PHARMACIES - Lampiao, Fanuel; Kafukiza, Samson; Msowoya, Denise; Phiri, Thokozire; Wyson, Lina; Alfazema, Louisa (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Kigelia africana fruit powder is being sold in Malawian retail pharmacies for the purported purpose of lowering blood sugar in diabetic patients when there is scant data on its hypoglycaemic activity. This study was aimed at evaluating the hypoglycaemic potential of the Kigelia africana fruit powder being sold in Malawian retail pharmacies. Materials and Methods: Hyperglycaemia was induced in rats via intra-peritoneal injection of dexamethasone. Albino rats were randomly allocated into five different groups of eight rats each. Group 1 consisted of non-hyperglycaemic rats receiving no treatment, group 2 consisted of hyperglycaemic rats receiving no treatment, group 3 consisted of hyperglycaemic rats receiving 25mg/kg of metformin, group 4 consisted of hyperglycaemic rats receiving 0.5mL of Kigelia africana fruit powder filtered solution, and group 5 consisted of hyperglycaemic rats receiving 1mL of Kigelia africana fruit powder solution. Results: The Kigelia africana fruit powder filtered solution administered to hyperglycaemic albino rats significantly lowered the sugar level which was comparable to the reduction caused by the pharmacological drug, metformin. Conclusions: Kigelia africana fruit powder has the potential of lowering glucose levels in white albino rats.